2018
DOI: 10.1177/1461444818804980
|View full text |Cite
|
Sign up to set email alerts
|

If software is narrative: Joseph Weizenbaum, artificial intelligence and the biographies of ELIZA

Abstract: Software is usually studied in terms of the changes triggered by its operations in the material world. Yet, to understand its social and cultural impact, one needs to examine also the different narratives that circulate about it. Software's opacity, in fact, makes it prone to being translated into a plurality of narratives that help people make sense of its functioning and presence. Drawing from the case of Joseph Weizenbaum's ELIZA, widely considered the first chatbot ever created, this paper proposes a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 46 publications
0
28
0
2
Order By: Relevance
“…A biography of Photoshop, for example, shows that material changes to its features over time as part of its various version upgrades prompted recurring debates about cultural value within the communities of practice who design and use it (Lesage, 2016). Similarly, Natale’s (2019) own biographical account of Joseph Weizenbaum’s early chatbot ELIZA shows how its material opacity led to its translation into a plurality of narratives that shaped people’s understandings of AI and chatbots. An example from this special issue is Bory’s (2019) examination of the narrativization of two formative events in AI’s introduction to the popular imagination.…”
Section: Towards a Biographical Approachmentioning
confidence: 99%
“…A biography of Photoshop, for example, shows that material changes to its features over time as part of its various version upgrades prompted recurring debates about cultural value within the communities of practice who design and use it (Lesage, 2016). Similarly, Natale’s (2019) own biographical account of Joseph Weizenbaum’s early chatbot ELIZA shows how its material opacity led to its translation into a plurality of narratives that shaped people’s understandings of AI and chatbots. An example from this special issue is Bory’s (2019) examination of the narrativization of two formative events in AI’s introduction to the popular imagination.…”
Section: Towards a Biographical Approachmentioning
confidence: 99%
“…This is a major warning because if the AI robot is hacked and turned against its purpose it would be a nightmare. Joseph Weizenbaum proposed that AI applications cannot understand, by definition, effectively reproduce certified human compassion and that the utilization of AI innovation in fields [25]. Weizenbaum was also reported that AI specialists (and a few rationalists) were eager to see the human personality as just a PC program (a position presently known as computationalism).…”
Section: Demerits Of Ai On Society and Mankindmentioning
confidence: 99%
“…Weizenbaum was also reported that AI specialists (and a few rationalists) were eager to see the human personality as just a PC program (a position presently known as computationalism). He also proposes that AI research depreciates human life [25]. Martin Ford reported that Automation, Accelerating Technology and the Economy of the Future, and others contend that particular artificial intelligence applications, robotics and different types of automation will eventually bring significant changes in job life that means huge unemployment as machines coordinate and surpass the ability of laborers to perform daily schedule and boring employments [26].…”
Section: Demerits Of Ai On Society and Mankindmentioning
confidence: 99%
“…The letter employs a biographical narrative for the electric pen – a device that, like a human life, ‘had its day in the sun’, that tried to hold its own, and now is fading away into a vast field. If the letter described the failure of anything, it described the failure of the narrative surrounding the electric pen, a flaw in the story by which people were meant to comprehend new technologies and to integrate them into the practices of their daily lives (Natale, 2018). It would appear that from this agent’s admission, the narrative of the electric pen was wrong from the beginning – ‘had it been launched in a different manner it could have held its own’.…”
Section: The Electrical Wonder: Performing the Modernmentioning
confidence: 99%